Palestinian Scientific Research from the Perspective of Bachelor's Students: Exploring Reality and Aspirations - Matar, Osama Issam; Jawabreh, Reem Mashhour; Radwan, Haya Yaser; Ayyash, Mohammad Shareef; Gharabeh, Thaher Mohamed; Alhajhamad, Abedelrahman Aqel; Abualrob, Ashraf Mohammed; Halabi, Aseel Adly; Abu Shomer, Diya Mohammed; Kaleef, Sherin Wael (Journal of Humanities & Social Sciences, 2023)
This study aims to identify the situation of Palestinian scientific research between reality and hope from bachelor students’ point of view. The researchers adopted the descriptive statistical approach due to its suitability to the nature of the study, which is based on describing the nature of Palestinian scientific research, and possible challenges faced by Palestinian researchers in their research career. The sample contains 432 male and female researchers, who were selected randomly. The researchers prepared a questionnaire consisting of 21 items as a study tool for data collection. The results show a number of challenges and obstacles faced by Palestinian researchers. The most noticed of which was the lack of funding for scientific research. Also, other challenges arise, like the lack of training opportunities for scientific research outside the framework of universities and the lack of knowledge on scientific research and publishing strategies. The study recommends a better funding, that is, the government should allocate a financial budget for scientific research, in addition to providing financial resources to train students and support them in the field of scientific research. Palestinian scientific research should be supported to advance on the international scene, through conferences participation.
Keywords: scientific research; challenges and obstacles; bachelor students; Palestine